Implacable Alpha - Gear, W. Michael (Gear, W. Michael. Team PSI series, 2022)
"Called the 'Ennoia, ' the woman who came within a heartbeat of killing prisoner Alpha in the Grantham parking garage is back. This time she's snatched Dr. Timothy Ryan. The Psi Team find themselves caught in a battle that has been raging across timelines for 2000 years. But, can they trust the Ennoia? Or is she using our timeline for her own purposes?"--Dust jacket flap.